Review of the CFC/ICCO/Bioversity project on cacao germplasm evaluation (1998-2010) - Medina, V.; Meter, A.; Demers, Nicole R.; Laliberte, B. (Bioversity International, 2017)
The CFC/ICCO/Bioversity project was in response to an urgent need to revitalize cacao breeding and research globally for increasing resistance to pests and disease. It aimed to strengthen national cacao improvement programmes and increase international collaboration by carrying out joint evaluation, selection and breeding activities in ten cocoa-producing countries. The project implemented in two phases – Phase I (1998- 2004) and Phase II (2004-2010), has been one of the most ambitious collaborative efforts in cacao breeding. With an understanding that a similar global collaboration is needed to tackle the impacts of climate change on cacao production, this review was developed in response to a request from the cocoa industry and research partners to evaluate the effectiveness of the project, identify key lessons learned for the implementation of new multisite evaluation field trials focused on increasing the resilience of cacao to the effects of climate change. The cacao research community will be able to use these lessons learned to be better prepared for, and more effective in, the execution of future collaborative research initiatives.